The Principle of a Single Estate and Its Role in Delimiting the Applicable Laws - Pacuła, Krzysztof (Problemy Prawa Prywatnego Międzynarodowego, 2020)
This paper argues that the principle of unity of succession is one of the key concepts of the Succession Regulation. By operation of this principle on the jurisdictional level, the Regulation tends to favor a perspective of a single Member State when it comes to all issues related to succession. The principle of unity of succession does not of course eliminate the need to proceed to the characterization and to delimitate the scopes of conflict of laws rules at stake. However, this principle — aiming to promote a unitary vision of a single estate in all the Member States bound by the Regulation — sets a tone for some interpretative techniques that tend to favor succession-related characterization of the issues having some importance in the context of succession with cross-border implications. According to the Author, effet utile-driven characterization, on the one hand, and succession-friendly characterization of the issues falling within ‘gray areas’ created by the operation of Article 1(2) of the Succession Regulation, on the other hand, are among them.